2018
DOI: 10.1080/2162402x.2018.1483303
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations of T cell cancer immune response with tumor aggressiveness in localized prostate cancer patients and disease reclassification in an active surveillance cohort

Abstract: Determining prostate cancer (PCa) aggressiveness and reclassification are critical events during the treatment of localized disease and for patients undergoing active surveillance (AS). Since T cells play major roles in cancer surveillance and elimination, we aimed to identify genetic biomarkers related to T cell cancer immune response which are predictive of aggressiveness and reclassification risks in localized PCa. The genotypes of 3,586 single nucleotide polymorphisms (SNPs) from T cell cancer immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Immunoproteasome-mediated proteolysis generates immunogenic epitopes presented by major histocompatibility complex (MHC) class I molecules. we have already confirmed the role of PSMB8 in the evolution of cutaneous squamous cell carcinoma, papillary thyroid carcinoma, and prostate adenocarcinoma, ( 13 - 15 ), In addition to the previously mentioned tumors, PSMB8 plays an inhibiting neovascularization role in glioma by regulating ERK1/2 and PI3K/AKT signaling pathways ( 16 , 17 ). These findings elucidate that the expression of PSMB8 is associated with multiple immune-related pathways in vivo, and that the gene may act as a powerful biomarker to determine the prognosis of a variety of cancers.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Immunoproteasome-mediated proteolysis generates immunogenic epitopes presented by major histocompatibility complex (MHC) class I molecules. we have already confirmed the role of PSMB8 in the evolution of cutaneous squamous cell carcinoma, papillary thyroid carcinoma, and prostate adenocarcinoma, ( 13 - 15 ), In addition to the previously mentioned tumors, PSMB8 plays an inhibiting neovascularization role in glioma by regulating ERK1/2 and PI3K/AKT signaling pathways ( 16 , 17 ). These findings elucidate that the expression of PSMB8 is associated with multiple immune-related pathways in vivo, and that the gene may act as a powerful biomarker to determine the prognosis of a variety of cancers.…”
Section: Resultssupporting
confidence: 77%
“…Another study on the functions of PSMB8 in the pathogenesis of mucinous ovarian cancer has confirmed that PSMB8 is an intermediary between the presentation of foreign antigens by MHC - I molecules and the irregular nuclear factor-light chain enhancer ( Nik/NF - kB ) pathway of activated B cells ( 27 ). Additionally, PSMB8 is involved in activating the PI3K/AKT pathway in acute myelogenous leukemia ( 28 ), and several studies have reported its contribution to the progression of cutaneous squamous cancer, papillary thyroid cancer, and prostate cancer ( 13 - 15 ). Several studies have proposed that PSMB8 works by promoting immune cell concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the relationship between Gleason scores (and BCR) and immune function ( 14 , 24 , 25 ), we evaluated the effect of COL5A2 on immune infiltration. Our results revealed that COL5A2 remarkably increased the numbers of macrophages, Th2 cells, and DCs in the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This study used data from a previously described cohort of patients with PCa enrolled at MDACC [ 10 , 11 ]. In brief, the cohort involved non-Hispanic white men with previously untreated PCa.…”
Section: Methodsmentioning
confidence: 99%